2009
DOI: 10.1007/s00428-009-0826-7
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4 and CEA can be mutually exchanged with confidence between both relevant three-marker panels (ER/Vim/CEA and ER/Vim/p16INK4) in distinguishing primary endometrial adenocarcinomas from endocervical adenocarcinomas in a tissue microarray study

Abstract: The accurate distinction between primary endocervical adenocarcinomas (ECA) and endometrial adenocarcinomas (EMA) may require the use of multiple ancillary monoclonal antibodies in panels of immunohistochemistry stains. In addition to reappraising the expressions of four commonly used individual monoclonal antibodies [estrogen receptor (ER), Vimentin (Vim), carcinoembryonic antigen (CEA), and p16(INK4)], this study was designed to investigate whether CEA and p16(INK4) can be effectively exchanged between two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The p16 INK4a marker appears to be a sensitive surrogate for the presence of HPV infection. Hence, p16 INK4a staining can be regarded as the second choice because p16 INK4a (+) favors the site of endocervical origin [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The p16 INK4a marker appears to be a sensitive surrogate for the presence of HPV infection. Hence, p16 INK4a staining can be regarded as the second choice because p16 INK4a (+) favors the site of endocervical origin [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Lamin may also affect the extracellular matrix by the closely connected network of actin-lamin links; this link is affected usually by oncogenes and may play a role in nuclear envelope distortion and in the margin irregularity in tumoral processes [36]. Vimentin is a 58-kDa glycoprotein that has been considered as a relevant tumor marker in distinguishing primary endometrial adenocarcinomas from endocervical adenocarcinomas [37]. Immunofluorescent stainings of surgical specimens have indicated that cervical carcinoma progression and cell invasion is accompanied by vimentin and epidermal growth factor receptor overexpression [38].…”
Section: Discussionmentioning
confidence: 99%